Analysis of current middleware used in peer-to-peer and grid implementations for enhancement by catallactic mechanisms - Pablo Chacin; Isaac Chao; Felix Freitag (Universität Bayreuth, Lehrstuhl für Wirtschaftsinformatik, 2005)
This deliverable describes the work done in task 3.1, Middleware analysis: Analysis of current middleware used in peer-to-peer and grid implementations for enhancement by catallactic mechanisms from work package 3, Middleware Implementation. The document is divided in four parts: The introduction with application scenarios and middleware requirements, Catnets middleware architecture, evaluation of existing middleware toolkits, and conclusions. – – Die Arbeit definiert Anforderungen an Grid und Peer-to-Peer Middleware Architekturen und analysiert diese auf ihre Eignung für die prototypische Umsetzung der Katallaxie. Eine Middleware-Architektur für die Umsetzung der Katallaxie in Application Layer Netzwerken wird vorgestellt.
urn:nbn:de:bvb:703-opus-3078
Keywords: 330; Grid Computing